The Effect of Using Some Cognitive-motor Abilities on Learning the Performance of Passing and Shooting Skills in Football for Pupils Ages (11-12) Years - Mohammed Hassan, Mohsen; Mohammed Jawad Al-Sayegh , Ali; Hassan Mohammed Jawad, Wissam (International Journal of Psychosocial Rehabilitation, 2020)
Through the experience of the researchers, as they are specialists in this field, they found that there is a difficulty facing students in mastering the stages of the motor performance of the passing and shooting skills on goal, which are the most important step in the success of the performance of these skills, and that learning the correct performance of these two skills gives a great motivation for students in mastering the rest of the stages These skills, through the application of some exercises of cognitive abilities, kinetic in the process of learning the stages of kinetic performance of the skill because of these cognitive abilities kinetic importance as a way to improve the way of performance and achieve effective learning of the skill, while the goal of the research is to identify the impact Some cognitive abilities - the kinematics in learning the performance of the passing and shooting skills of football for students between the experimental and experimental groups in the post-test. The researchers used the experimental approach to design equivalent groups with pre- and post testing, and the research community was identified from the sixth primary grade students in Jaber Al Ansari Primary School for boys in the governorate Najaf at the age of (11-12) years for the academic year (2019-2020), as the number of community members reached (115) students distributed over (3) people, and (20) students were chosen from one division of them by lot and they were divided into two equal groups (10) Students of all groups So that the first group is experimental, it applies exercises for some of the cognitive motor abilities, and the second group is applied to the teacher’s method (followed). As for the conclusions, they were for the exercises using some cognitive-motor abilities in learning the passing and shooting skills of football for pupils ages 11-12 years to have a positive effect-—using analysis, presentation, and correcting errors in the performance of passing and shooting skills. An effect in developing the motor performance of football for pupils ages 11-12 years is attention to the means of clarification, presentation, and correction, because it works to clarify the image of the stages of technical performance of the skills of students with studies and research and other basic skills differently to take advantage of them to reveal the strengths and weaknesses of other types of basic skills in order to develop the level of performance of the players and for other age groups.